The public eye - Franklin, Howard; Pesci, Joe; Hershey, Barbara, 1948-; Zemeckis, Robert, 1952-; Universal Pictures (Firm) (California : Universal, 2011)
Joe Pesci atarts as a brash, 1940's tabloid potographer whose camera leads him into a shadowy underworld of mob violence, unlikely romance and dangerous corruption in The Public Eye. Prowling the crime-ridden, midnight streets of New York, freelance shutterbug Leon "Bernzy" Bernstein (Pesci) captures life's grim side in his lens - and dreams of the day his pictures will be recognized as works of art. When ravishing nightclub owner Kay Levitz (Barbara Hershey) lures Bernzy into investigating the thugs trying to muscle in on her business, he finds himself mixed up in a realm of blacik market scams and mafia gang war. Now, Bernzy's either going to take the fall or take the one-in-a-million shot that could cange his life forever.
Originally released as a motion picture in 1992.
Music by Mark Isham ; editor Evan Lottman A.C.E. ; production designer Marcia Hinds-Johnson ; director of photography Peter Suschitzky.
Joe Pesci, Barbara Hershey.
R Violence
DVD ; region 1 ; anamorphic widescreen, aspect ratio 1.85:1 ; Dolby Digital 2.0 mono.
English dialogue
Keywords: Photojournalism -- United States -- Drama; Feature films